2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30318
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Power and Energy Engineering Minor with Limited Resources: First Results and Lessons Learned

Abstract: He is holding one PHD in power engineering and other one in physics. Before joining to Southern University Dr. Belu hold faculty, research and industry positions at universities and research institutes in Romania, Canada and United States. He also worked for several years in industry as project manager, senior engineer and consultant. He has taught and developed undergraduate and graduate courses in power electronics, power systems, renewable energy, smart grids, control, electric machines, instrumentation, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Second reason was the initial lack of adequate educational laboratory infrastructure, insufficient fully operation laboratory workstations, obsolete, incomplete and old equipment making all power engineering, electric machines or power electronics settings, being no exception hard to set, run and perform. However, the things are about to change due to a $2,000,000 generous donation for our college from the Entergy Corporation, with in addition the commitment of our state governor to match the donation [34][35][36]. About a quarter of this gift is designed to support the power and energy minor laboratory and research infrastructure.…”
Section: Pedagogical Approach Rationale and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second reason was the initial lack of adequate educational laboratory infrastructure, insufficient fully operation laboratory workstations, obsolete, incomplete and old equipment making all power engineering, electric machines or power electronics settings, being no exception hard to set, run and perform. However, the things are about to change due to a $2,000,000 generous donation for our college from the Entergy Corporation, with in addition the commitment of our state governor to match the donation [34][35][36]. About a quarter of this gift is designed to support the power and energy minor laboratory and research infrastructure.…”
Section: Pedagogical Approach Rationale and Methodsmentioning
confidence: 99%
“…In our view, power electronics and renewable energy are two important topics for today power and energy engineering students. In many cases, the two topics are inextricably intertwined [31][32][33][34][35][36]. As the renewable energy sector grows, the needs for engineers qualified to design such systems grows as well.…”
Section: Course Objectives Goals Content Structure and Projectsmentioning
confidence: 99%
“…The overall objective of this course is to provide students with both the science and technology of different energy sources, alternative and renewable sources, power system operation, as well as the policies that heavily influence this industry. The course main goals involve student in-depth understanding of the energy sources, their characteristics and operation, types of the used fuels, energy system components, structure, configurations, types and characteristics of the common generation units, grid integration issues of the renewable energy and distributed generation units, major types of alternative energy sources, their characteristics and performances, assessment and analysis, the infrastructure of existing energy systems, economic and environmental issues of the current energy generation, transformation and uses [15][16][17][18][19][20][21][22][23][24]. Notice that during the first week, students must read the syllabus, acknowledge the fact that they read it and understood what is expected of them.…”
Section: Course Content and Structurementioning
confidence: 99%
“…We are realizing that this is one of the most challenging courses to set, design and offer due to the need of the student to have an expertise and background in many engineering and applied sciences disciplines, from power engineering, electric machines, to thermal sciences, electrochemistry, fluid mechanics to computer science and lack of easily accessible relevant information. Moreover, during recent years, the traditional education systems have witnessed significant transformations aligned to research related to how learning occurs, new educational technologies, and the resurgence new standards to design learning environment and delivery modalities to foster deeper learning competencies and accommodate students with various learning needs [18][19][20][21][22][23][24]. In the recent years, the adoption of innovate the learning process and to increase college affordability and success through online and e-Learning, or zero-textbook-costs has been at the core of 21st century curricular revisions agend.…”
Section: Course Content and Structurementioning
confidence: 99%
“…Kerestes et al reported an enhanced workforce development study through a consortium that includes twelve universities, seventeen industry partners, and two national labs in order to enhance curriculum development and education in the study of electrical power and distributed energy resources [13]. Belu et al suggested methods to revitalize a power engineering program with an enhanced major and a new minor program development, while promoting new concepts of smart grids, energy management, and renewable energy systems with support from local and regional industry [14]. Powell and Hayt developed a low-voltage microgrid for experiments in renewable energy distribution that exposed undergraduate engineering students to power generation, grid, and distributed related topics early in a power curriculum that enhanced the students' understanding of both renewable energy integration as well as conventional grid [15].…”
Section: Introductionmentioning
confidence: 99%